Agricultural-industrial integration and new applications of natural fibres: jute floodplain cropping in the Amazon reborn? - S.M. Bicalho, Ana Maria (Journal for Geography, 2009)
In recent years natural fibre production has taken on considerable appeal because of new industrial applications in environmental friendly products and growing demand for fibres could contribute to social welfare of poor farmers in developing countries. The new uses of natural fibres are part of highly technical green solutions for problems in the industrial and consumption regions but it may be asked whether this demand really addresses social and ecological issues in regions of primary production. These issues are examined in the Brazilian Amazon where recently a composite fibre sheet factory was opened and fibre cropping is making a comeback after decades of economic stagnation. It is shown here that the expansionof the activity, while significant, has not yet reached the scale of the past, but the market is promising, particularly in the automotive industry, which could further stimulate jute and malva production in the region.
Keywords: natural fibres; new industrial applications; agricultural-industrial integration; Amazon region; Brazil